Mechanical And Electrical Properties Of Short Carbon Fibre Reinforced Polycarbonate Composites - Yap, Cia Ling (Universiti Sains Malaysia, 2018)
A series of composites was prepared using polycarbonate (PC) as the matrix, reinforced with short carbon fibre (SCF) at different weight fractions. The composites were compounded by single screw extruder and specimens were prepared by injection moulding machine. The effect of fibre weight fractions on the mechanical and electrical properties of SCF reinforced polycarbonate composite was studied. The test specimens were fabricated in accordance to the ASTM specifications. The mechanical properties of the composites were characterized by tensile, flexural and fracture toughness tests, while the morphological properties were characterized by scanning electron microscope (SEM). In addition, electrical properties were evaluated by surface resistivity test. Cox-Krenchel and rule of mixtures (RoM) were used to predict theoretical tensile moduli of the composites. Experiment results revealed that density of the composites increased with the addition of SCF. Fibre length was found to be greatly reduced during processing the of composites. Higher mean fibre length tends to provide better reinforcement effect, thus enhanced mechanical properties. Incorporation of SCF improved the strength of the composite, and the effect was more prominent at higher weight fraction of SCF. With increasing SCF content, the surface resistivity reduced drastically with the percolation threshold lie in between 10% - 14% of SCF weight fraction. Cox-Krenchel model showed to be a good approximation to predict the composites’ tensile modulus. 14% SCF reinforced PC composite which was obtained from commercial compound proved the effective extrusion compounding of these self-compounded composites (5%, 10% and 15% SCF), by possessing intermediate properties in between 10% and 15% SCF reinforced PC composites as expected.